Ordinance no. 12, § 2, OXFORD EAGLE, Jul. 7, 1898, at 2 (Oxford, Mississippi) - (:unkn) unknown (General Publisher, 1898)
Prohibited brandishing deadly weapons in a rude, angry, or threatening manner.
--
Keywords: BRANDISHING